The ARTISSE intrasaccular device for intracranial aneurysm treatment: short-term, mid-term and long-term clinical and angiographic results. (5th October 2021) - Piotin, Michel; Fahed, Robert; Redjem, Hocine; Smajda, Stanislas; Desilles, Jean Philippe; Escalard, Simon; Maïer, Benjamin; Hebert, Solène; Delvoye, François; Mazighi, Mikael; Blanc, Raphaël
Abstract : Background: The concept of intra-aneurysmal flow disruption has emerged as a new paradigm for the treatment of primarily bifurcation aneurysms. The purpose of this study was to determine the clinical and angiographic outcomes of patients treated with the new ARTISSE intrasaccular device (ISD). Methods: Selected patients with bifurcation aneurysms that matched the indications of the ARTISSE ISD defined by the manufacturer were treated in a single center. Clinical and angiographic follow-up was conducted at 6 and 36 months. Aneurysm occlusion was assessed using the Raymond–Roy classification scale. Results: Nine subjects with nine unruptured bifurcation aneurysms were enrolled. Mean aneurysm size was 7.2±1.2 mm (range 5.5–9.7 mm). An adequate aneurysm occlusion (defined as a complete occlusion or a neck remnant) was achieved in 6/9 patients (66.7%) at 6 months and 4/7 patients (57.1%) at 36 months follow-up. Two of the nine subjects experienced a major stroke (22.2%), including one on postoperative day 1 due to a procedure-related parent vessel occlusion and subsequent ischemic stroke. The other major stroke occurred within the 36-month follow-up period during treatment of a separate aneurysm with coils, leading to perforation with hemorrhagic stroke causing a permanent neurological deficit. Conclusion: The ARTISSE ISD was successfully deployed in all nine cases. There were, however, several procedure-related complications and results in terms of angiographic aneurysm occlusion were modest.